2022
DOI: 10.1080/13880209.2021.2014895
|View full text |Cite
|
Sign up to set email alerts
|

Folium Ginkgo extract and tetramethylpyrazine sodium chloride injection (Xingxiong injection) protects against focal cerebral ischaemia/reperfusion injury via activating the Akt/Nrf2 pathway and inhibiting NLRP3 inflammasome activation

Abstract: Context Folium Ginkgo extract and tetramethylpyrazine sodium chloride injection (Xingxiong injection) is a compound preparation commonly used for treating cerebral ischaemia/reperfusion injury in ischaemic stroke in China. However, its potential mechanisms on ischaemic stroke remain unknown. Objective This study explores the potential mechanisms of Xingxiong injection in vivo or in vitro. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…ELISA kits were used according to the manufacturer’s instructions and a previously described method [ 12 , 46 ] to quantify IL-6, TNF-α, MCP-1, T-AOC and 4-HNE in serum.…”
Section: Immunofluorescence Stainingmentioning
confidence: 99%
“…ELISA kits were used according to the manufacturer’s instructions and a previously described method [ 12 , 46 ] to quantify IL-6, TNF-α, MCP-1, T-AOC and 4-HNE in serum.…”
Section: Immunofluorescence Stainingmentioning
confidence: 99%
“…We used previously reported information to explore the mechanism of TCM in the treatment of stroke. 7,8 Network pharmacology analysis was based on 277 compounds with potential biological activity, 2846 corresponding protein targets, and 3777 disease targets in WYHYF to construct a "drug-ingredient-target-disease" network. Pathway enrichment analysis suggested that inflammation is closely related to cerebral ischemia-reperfusion, and the inflammatory signaling pathway may play an important role in treating cerebral ischemia-reperfusion using WYHYF.…”
Section: Discussionmentioning
confidence: 99%
“…We used previously reported information to explore the mechanism of TCM in the treatment of stroke. 7,8…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/Akt pathway activation can promote Nrf2 nuclear translocation ( Martin et al, 2004 ; Zhai et al, 2018 ). TMP sodium chloride injection was reported to enhance the expression of HO-1 by activating the PI3K/Akt/Nrf2 signal pathway ( Zhu et al, 2022 ). At the same time, the expression levels of IL-1β, caspase-1, and NOD-like receptors family pyrin domain containing 3 (NLRP3) were significantly decreased by the treatment of TMP sodium chloride injection ( Zhu et al, 2022 ).…”
Section: Effects Of Tetramethylpyrazine On Central Nervous System Dis...mentioning
confidence: 99%